Sinergi Media Pembelajaran Digital dan Faktor Psikologis Siswa dalam Pembelajaran - Prajihan Nisrina; Saepul Anwar; Nurti Budiyanti (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
Digital transformation in education has encouraged the use of various digital learning tools to improve the learning process. However, the success of these digital tools depends not only on the technology itself, but also on the students' psychological factors. This study aims to systematically analyze how digital learning tools and students' psychology work together to affect learning quality, based on scientific publications from 2023 to 2025. The research uses a qualitative approach with a Systematic Literature Review (SLR) method, following the PRISMA 2020 guidelines. The data comes from Scopus-indexed scientific articles published between 2023 and 2025. Based on specific inclusion and exclusion criteria, 8 articles were selected. These eight articles show that the success of digital learning tools is strongly influenced by students' psychology, especially student engagement, learning motivation, self-efficacy, autonomy, competence, and relatedness. Digital tools that are interactive, adaptive, and personal can boost students' learning engagement, sense of competence, and motivation. On the other hand, technology becomes less effective if students' social, emotional, and psychological needs are not met. The results show that digital learning tools and psychological factors support each other to create a more effective, meaningful, and student-centered learning experience. This study helps improve our understanding of how educational technology and learning psychology connect, which can be used to develop more adaptive and human-centered digital learning.